The Politicization of Population Data Governance in the Perspective of Principal-Agent: Case Study in Indonesia - Misran; Muallidin, Isnaini; Nanaman, Marilou Siton; Prasetyo, Satria Iman (Jurnal Bina Praja, 2022)
Indonesia is one of the list of developing countries in the world. The thing that is most often found in developing countries is vast populations. As one of the countries with the highest demographic bonus, Indonesia ranks at the top of the list for the world's population density. The complexity of the problem of population data in Indonesia has become an enormous homework for the government. The issue of this occupation data has haunted the Indonesian government for a long time. This study aims to analyze the politicization of Indonesian population data governance from the moral agent perspective. This study uses a qualitative approach. Sources of data were collected from previous studies related to the research topic by analyzing the phenomena in Indonesia. The findings of this study reveal the game of politicians and bureaucracy in playing population data. The game is in the form of politicizing data based on political interests. In the principal-agent perspective, where the contract is signed under asymmetric information when one party knows certain relevant things that the other party does not know